2014
DOI: 10.5624/isd.2014.44.1.21
|View full text |Cite|
|
Sign up to set email alerts
|

Conversion coefficients for the estimation of effective dose in cone-beam CT

Abstract: PurposeTo determine the conversion coefficients (CCs) from the dose-area product (DAP) value to effective dose in cone-beam CT.Materials and MethodsA CBCT scanner with four fields of view (FOV) was used. Using two exposure settings of the adult standard and low dose exposure, DAP values were measured with a DAP meter in C mode (200mm×179 mm), P mode (154 mm×154 mm), I mode (102 mm×102 mm), and D mode (51 mm×51 mm). The effective doses were also investigated at each mode using an adult male head and neck phanto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Bechara et al 39 also encouraged case-bycase decision-making on exposure factors, as they found that when imaging endodontically treated root fractures using a 360°as opposed to 180°rotation did not improve sensitivity but did improve specificity by reducing artefact, which could potentially reduce the number of patients having to undergo unnecessary treatment. birpublications.org/dmfr Dentomaxillofac Radiol, 45,20150254 Dose optimization in dental CBCT using kV and mAs: systematic review Goulston et al…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bechara et al 39 also encouraged case-bycase decision-making on exposure factors, as they found that when imaging endodontically treated root fractures using a 360°as opposed to 180°rotation did not improve sensitivity but did improve specificity by reducing artefact, which could potentially reduce the number of patients having to undergo unnecessary treatment. birpublications.org/dmfr Dentomaxillofac Radiol, 45,20150254 Dose optimization in dental CBCT using kV and mAs: systematic review Goulston et al…”
Section: Resultsmentioning
confidence: 99%
“…During the first "screening" stage, the primary author (RG) read the journal titles and full abstracts of the studies found, to see if they fitted the eligibility criteria; those that met the criteria went through to stage two, where the primary author read the full-text article to ensure the studies continued to meet the pre-defined eligibility criteria. Where the primary author was uncertain about the eligibility of a study, this was resolved by discussion Dentomaxillofac Radiol, 45,20150254 birpublications.org/dmfr Dose optimization in dental CBCT using kV and mAs: systematic review with the other authors. This occurred on three occasions, and on all three occasions, it was decided that the study being considered did not meet the eligibility criteria; so, these studies were excluded from the review.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations